2018
DOI: 10.5296/ijhrs.v8i2.12932
|View full text |Cite
|
Sign up to set email alerts
|

Youngsters Perception Toward Social Networking Advertising: Does Social Media Advertising Factors Still Matter?

Abstract: Social Networking Sites (SNS) including Facebook, Instagram, Twitter, Linkedin, Flickr and My Space are significantly grown in popularity among youngster and has become powerful media for advertisers as well as advertising industry all around the world. Advertising via social networking platform allows segmentation of advertising activities based on customers' demographic. Hence, it is different from social medial advertising which is public-focused based. Thus, this study aims to explore does the important su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(19 reference statements)
0
1
0
1
Order By: Relevance
“…Instagram advertisement merupakan salah satu bentuk metode untuk memasarkan produk yang menyasar pada target konsumen. Media sosial termasuk Facebook, Instagram, Twitter, Linkedin, Flickr dan MySpace semakin popular pada kalangan milenial dan telah menjadi media yang kuat untuk industri periklanan di dunia dan faktor informativeness terbukti dapat mempengaruhi persepsi milenial terhadap iklan pada media sosial (Kowang et al, 2018).…”
Section: Pendahuluanunclassified
“…Instagram advertisement merupakan salah satu bentuk metode untuk memasarkan produk yang menyasar pada target konsumen. Media sosial termasuk Facebook, Instagram, Twitter, Linkedin, Flickr dan MySpace semakin popular pada kalangan milenial dan telah menjadi media yang kuat untuk industri periklanan di dunia dan faktor informativeness terbukti dapat mempengaruhi persepsi milenial terhadap iklan pada media sosial (Kowang et al, 2018).…”
Section: Pendahuluanunclassified
“…One of the main challenges revolves around consumer's trustworthiness of the food and beverage served, especially in the context of online businesses. The issue of trustworthiness continuing to be a central focus on social media advertising (Kowang et al, 2018). Kumar and Pradhan (2018) reported that consumer trust in social media is currently low and it is not a static concept but changes over time hence trust management is becoming vital in social media marketing for organizations.…”
Section: Introductionmentioning
confidence: 99%